6x2+5x+1 = (3x+1)(2x+1) when factored
999 and 1
1st term is 1 to the power of 1 = 1 2nd term is 2 to the power of 2 = 4 3rd term is 3 to the power of 3 = 27 4th term is 4 to the power of 4 = 256
14
sorry if this is worded weirdly, im 11 so... -2 to the power of 3 is -2 x -2 x -2 anything to the 0th power is 1 then it becomes a fraction so like 2 to the -2 power is 1/2 to the 2nd power so 2 to the -3rd is 1/2 to the 3rd so 1/8 * * * * * A negative power is a reciprocal of the positive power. So (-2)-3 = 1/((-2)3 = 1/[(-2)*(-2)*(-2)] =1/(-8) = -1/8
Infinity.
(x + 4)(x2 - x - 1)
(x + 4)(x2 - x - 1)
(x + 4)(x2 - x - 1)
Assuming this is your original formula: -3p3+ 5p + -2p2 + -4 - -12p + 5 - -8p3You combine like terms, where the p exponent is the same, to produce:5p3 - 2p2 + 17p + 1
Factor it. y(4y - 1)(3y - 2) = 0 y = 0, 1/4, 2/3
7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a
the answer is 10 and 3 6th
Yes.
10 ( x = -3)
It is -6.
3³ + 1³ = 27 + 1 = 28